Antibacterial activity of N-halamine decorated mesoporous silica nanoparticles. (September 2017) - Xu, Jiarong; Zhang, Yu; Zhao, Yanbao; Zou, Xueyan
Abstract: N-halamine decorated mesoporous silica nanoparticles (mSiO2 /halamine NPs) were prepared by coating mSiO2 NPs with poly (1-allylhydantoin-co-methyl methacrylate) (AH-co-MMA) by the aid of the radical polymerization, followed by chlorination treatment. The sterilizing effect on the bacterial strain is investigated by incubating Staphylococcus aureus ( S. aureus ) and Escherichia coli ( E. coli ). Results indicated that the mSiO2 /halamine NPs had excellent antibacterial activity and no significant change occurred in antibacterial efficiency after five recycle experiments. Highlights: Allylhydantoin based polymer was prepared by polymerization. N-halamine antimicrobial agent was obtained by chlorination. mSiO2 /halamine NPs displayed excellent antibacterial activity.